2020
DOI: 10.3389/fbioe.2020.00383
|View full text |Cite
|
Sign up to set email alerts
|

3D Graphene Scaffolds for Skeletal Muscle Regeneration: Future Perspectives

Abstract: Although skeletal muscle can regenerate after injury, in chronic damages or in traumatic injuries its endogenous self-regeneration is impaired. Consequently, tissue engineering approaches are promising tools for improving skeletal muscle cells proliferation and engraftment. In the last decade, graphene and its derivates are being explored as novel biomaterials for scaffolds production for skeletal muscle repair. This review describes 3D graphene-based materials that are currently used to generate complex struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 77 publications
1
27
0
Order By: Relevance
“…Particularly, Bonferroni- post hoc analysis and quantification of stained mineral deposition ( Figure 9C ) revealed that mineral deposition on the 3D RGO/Alg scaffolds in differentiation medium was significantly higher compared to all the comparisons. This finding is consistent with previous reports on osteogenic induction of stem cells by 3D graphene scaffolds ( Crowder et al, 2013 ; Palmieri et al, 2020 ). It is worth noting that L -ascorbic acid-2-phosphate in differentiation medium can de-crosslink 3D Alg scaffolds (totally dissolving after Day 3), but RGO coated 3D Alg scaffolds remain intact for over 3 weeks due to the protective RGO coating.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Particularly, Bonferroni- post hoc analysis and quantification of stained mineral deposition ( Figure 9C ) revealed that mineral deposition on the 3D RGO/Alg scaffolds in differentiation medium was significantly higher compared to all the comparisons. This finding is consistent with previous reports on osteogenic induction of stem cells by 3D graphene scaffolds ( Crowder et al, 2013 ; Palmieri et al, 2020 ). It is worth noting that L -ascorbic acid-2-phosphate in differentiation medium can de-crosslink 3D Alg scaffolds (totally dissolving after Day 3), but RGO coated 3D Alg scaffolds remain intact for over 3 weeks due to the protective RGO coating.…”
Section: Resultssupporting
confidence: 94%
“…For example, coating graphene onto 3D printed scaffolds should endow 3D structures with mechanical strength and cytocompatibility ( Li et al, 2017 ). In addition, graphene-based structures have been shown to support in vivo bone regeneration by providing physicochemical cues and through the enhancement of material biocompatibility ( Liu et al, 2019 ; Palmieri et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, considering that growth factors are expensive and degrade rapidly, other strategies may be applied, including the use of fugitive inks, the employment of sandwiched constructs, the use of hollow fibers, or the combination of different additive manufacturing technologies operating across scales and employing varied materials. [165] In the area of carbon-based materials, the utilization of 3D printed graphene and CNTs, [61,140] with hollow micro-tubular structures, might synergize with endothelial cells and VEGF and support blood vessel growth. In the area of muscular repair, carbon nanotubes have been [168] found useful as VEGF carriers, so several types of CNTs-based composites may benefit from this carry and delivery ability.…”
Section: Microvascular Complexity In Carbon-based Solutionsmentioning
confidence: 99%
“…[48,54] The high tensile strength (⩾50 GPa), high Young's modulus (⩾1 TPa), and high aspect ratio long tubular shape of CNTs make them highly suitable for collagen fibers. [55][56][57] Apart from articular tissue regeneration, the biomechanical versatility of carbon-based materials has expanded other territories as well, including neural, [58] skin, [59] cardiac, [60] musculoskeletal, [61,62] and chondral [63] tissue engineering.…”
Section: Properties Related To Scaffolding Materialsmentioning
confidence: 99%
“…Some claimed that graphene and its derivatives possessed huge potential in biological and medical fields. Previous literature reported that graphene could regulate cell attachment, migration, differentiation, and viability 17 . The GO displayed antibacterial ability by disrupting E. coli bacterial cell membranes, decreasing the viability by over 90%, and elucidating strong oxidative stress 18 .…”
Section: Introductionmentioning
confidence: 99%